Effect of loss of correction on functional outcomes in thoracolumbar burst fractures treated with short segment posterior instrumentation - Doğan, Özgür; Çalışkan, Emrah; Gencer, Batuhan; Biçimoğlu, Ali (Journal of Surgery and Medicine, 2019)
Aim: Burst fractures are defined as vertebra fractures involving the anterior and middle columns and are associated with kyphotic deformity and retropulsion of bone fragment into the spinal canal. Although their treatment is controversial in the literature, use of transpedicular screws and short segment posterior instrumentation are increasingly common practices. The aim of this study is to investigate the radiological and functional outcomes of thoracolumbar vertebra burst fractures treated with short segment posterior instrumentation and to examine the effects of postoperative correction loss on these results. Methods: Patients who were surgically treated for thoracolumbar burst fractures and prospectively followed-up between 2000-2003 were scanned retrospectively for this cohort study. 48 patients were included in the study, of which 18 were females (37.5%) and 30 were males (62.5%). Denis Pain Scale (DPS) and Denis Work Scale (DWS) were used for functional analysis. Cobb angles that were measured preoperatively, on the first postoperative day, and at the last follow-up visit were used for evaluation of radiological outcomes. Spinal stenosis and remodelization rates were also calculated by computerized tomography obtained preoperatively and at the last follow-up. One-way ANOVA and Pearson correlation tests were used for statistical analysis. Results: No patient had any chronic pain complaints, and none were unable to work. The mean Cobb angles in the preoperative, early post-operative and final controls were measured as 23.2, 4.9, and 12.3 degrees, respectively. While preoperative mean Cobb angle and mean correction were positively correlated (r=0.85, P<0.001), there was no correlation between preoperative mean Cobb angle and loss of correction (r=0.27, P=0.43). There was a correlation between correction and loss of correction (r=0.38, P=0.008). Spinal stenosis, which was 35.7% preoperatively, reduced to 17.1% in the last follow-up. The mean remodelization was 51.3%, which was significant (P<0.001). Loss of correction was found significant in patients with poor DWS (P=0.003), and no such relationship was found in DPS. No correlation was found between the Cobb angle at the last follow-up, DPS and DWS. Conclusion: In conclusion, the loss of correction after short segment posterior instrumentation and fusion surgery is significantly higher in thoracolumbar burst fractures, especially when intraoperative correction exceeds 15 degrees. Denis Work Scale was significantly worse in patients with loss of correction above 10 degrees. The degree of loss of correction at the last follow-up is directly related to clinical and functional outcomes.